Implementasi Manajemen Sumber Daya Manusia dalam Meningkatkan Mutu Pendidikan di SMA Negeri 1 Bandar Khalipah - Winne Gultom; Robinhot Sihombing; Endang Manullang; Abai Tambunan (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the implementation of management regarding Human Resources, in order to improve the quality of education at SMA Negeri 1 Bandar Khalipah. Effective human resource management is a key to achieving a quality education goal. This study uses a qualitative approach with a case study method. The methods used to collect data are by conducting observations, interviews, and documentation. Data analysis is carried out using data reduction techniques, data presentation, and drawing conclusions. As for checking the validity of the data, it is by using triangulation of methods and sources. The results of this study will later present a description of the implementation of Human Resource Management to improve the quality of education at SMA Negeri 1 Bandar Khalipah by: 1) Analysis of the work carried out by the principal on educational and teaching staff, 2) Very comprehensive and structured human resource planning in the management of educational and teaching staff, 3) Procurement of human resources involves various stages and depends on the status of prospective educators (Honorary and PNS), 4) Selection of human resources involves various different stages for prospective educators, CPNS selection is stricter and more formal while honorary is more flexible, 5) Orientation of human resources involves stages and depends on the status of honorary or PNS, for honorary workers it is more flexible with an observation period while PNS is structured and comprehensive, 6) Appointment and placement of human resources depends on the status of honorary employees or PNS, honorary workers are placed according to the orientation period if accepted before the opening of a new class while PNS are based on SK and qualifications, 7) Compensation of human resources depends on employee status and applicable regulations, 8) Development of human resource careers human resources that should involve strategies and programs, both internal and external, 9) Evaluating human resource performance is done with various methods and frequencies, 10) Dismissal and termination of employment of human resources in this school depends on the conditions of the work contract, teacher requests and policies from the head of the education office and the principal. This study found that active participation from all parties in the school, including the principal, teachers, and staff plays an important role in supporting the improvement of the quality of education. This study concludes that in order to obtain quality human resources, in its management, it is necessary to implement good and correct human resource management so that it is in accordance with the expected needs.